Evaluation of spent oil shale as concrete aggregate - Gopal, More Sharad; Cook, David J.; Pama, Ricardo P.; Tanabe, T.; The Keidanren Foundation, Japan (Bangkok : Asian Institute of Technology, 1977)
The construction industry which requires large quantities of low cost raw materials has long provided potential outlets for industrial by-products and waste materials. The type of industrial waste product considered in this thesis is spent oil shale which has an oil content of 0.6%. The properties of concrete made with spent oil shale as (a) fine aggregate, (b) coarse aggregate and (c) both coarse and fine aggregate were investigated. Swelling and shrinkage strains were measured up to 90 days. Repeated wetting and drying aspect of durability was studied. The concrete mixes were designed for a 28-day compressive strength of 3,000 and 6,000 psi. Concrete made with oil shale as coarse aggregate showed higher values of shrinkage and swelling compared with those of concrete made with shale as fine aggregate. Spent oil shale can be used as fine aggregate to obtain adequate compressive strength. However, concrete made with spent oil shale as coarse aggregate showed ultimate compressive strength limited to a maximum of about 4,000 psi. The durability characteristics of all concrete specimen followed similar patterns.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1977
Keywords: Oil-shales; Aggregates (Building materials)